REGULATORY HARMONIZATION OF NOTARIAL LAW IN THE ERA OF SMART CONTRACTS: TOWARDS THE LEGALIZATION OF CYBER NOTARY IN INDONESIA - Iqbal Habibie; Nuzulia Kumala Sari; Moh. Ali (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The development of blockchain technology and smart contracts has transformed the mechanisms governing the formation and execution of legal relationships in digital transactions. This transformation poses significant challenges to Indonesia's notarial system, as the existing regulatory framework continues to rely on conventional authentication through physical presence, paper-based documentation, and direct verification, while the legal framework governing cyber notary remains insufficient. This study aims to analyze the urgency of legalizing cyber notary through the harmonization of notarial regulations in response to the advancement of smart contracts. The research employs a normative legal method using statutory, conceptual, and comparative approaches, with a prescriptive analysis of notarial law and electronic transaction regulations. The findings reveal regulatory disharmony concerning the recognition of electronic deeds, digital identity verification, virtual appearances of parties, and the authority of notaries in blockchain-based transactions, resulting in legal uncertainty and limiting the optimal role of notaries within the digital legal ecosystem. Based on these findings, the study recommends regulatory harmonization through the formal legal recognition of cyber notary, the strengthening of electronic authentication mechanisms, the regulation of virtual appearances of parties, the recognition of electronic deeds as authentic legal instruments, and the authorization of notaries to verify smart contracts in blockchain-based transactions. These recommendations provide a fundamental basis for strengthening legal certainty, legal protection, and the institutional capacity of the notarial profession in responding to the ongoing transformation of the digital legal landscape. ABSTRAK Perkembangan teknologi blockchain dan smart contract telah mengubah mekanisme pembentukan dan pelaksanaan hubungan hukum dalam transaksi digital. Perubahan tersebut menghadirkan tantangan bagi sistem kenotariatan di Indonesia karena regulasi yang berlaku masih bertumpu pada autentikasi konvensional melalui kehadiran fisik, dokumen tertulis, dan verifikasi langsung, sementara pengaturan mengenai cyber notary belum memiliki landasan hukum yang memadai. Penelitian ini bertujuan menganalisis urgensi legalisasi cyber notary melalui harmonisasi regulasi kenotariatan sebagai respons terhadap perkembangan smart contract. Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif yang dianalisis secara preskriptif terhadap ketentuan hukum kenotariatan serta hukum transaksi elektronik. Hasil penelitian menunjukkan adanya disharmoni regulasi terkait pengakuan akta elektronik, verifikasi identitas digital, kehadiran virtual para pihak, dan kewenangan notaris dalam transaksi berbasis blockchain, yang berdampak pada munculnya ketidakpastian hukum serta belum optimalnya peran notaris dalam ekosistem digital. Berdasarkan temuan tersebut, penelitian merekomendasikan harmonisasi regulasi melalui pengakuan yuridis cyber notary, penguatan mekanisme autentikasi elektronik, pengaturan kehadiran virtual para pihak, pengakuan akta elektronik sebagai alat bukti autentik, serta pemberian kewenangan kepada notaris untuk melakukan verifikasi smart contract dalam transaksi berbasis blockchain. Rekomendasi tersebut menjadi fondasi bagi penguatan kepastian hukum, perlindungan hukum, dan peningkatan kapasitas kelembagaan kenotariatan dalam menghadapi transformasi hukum di era digital.